Evaluasi Pelaksanaan Digitalisasi Penyiaran Pada LPP TVRI Jawa Timur - Purwanto; Tituk Utari (HERITAGE, 2023)
LPP TVRI East Java station has carried out preparations for digital broadcast trials on channel 35 UHF starting in 2015. Migration of television broadcasting systems from analog to digital until the time the research was carried out had not been fully carried out because it encountered several obstacles including problems related to government policies which postponed the implementation of full digital broadcasts. The research objective was to evaluate the implementation of digital broadcasting at LPP TVRI East Java. This study uses a type of qualitative research method by analyzing primary data and secondary data descriptively. The implementation of research has been carried out and obtained results regarding the implementation of digital broadcasts on TVRI East Java. Lack of human resources, especially those in charge of transmission stations, both in terms of number and competency that can support the target of the digital broadcasting era. The need for equipment support, spare parts and other back up equipment, to anticipate technical problems so that digital broadcasts can continue to run every day. LPP TVRI East Java starting November 2, 2022 and all terrestrial transmissions must have carried out full digital broadcasts. Having a capacity of 32 MB, LPP TVRI East Java is capable of broadcasting 8 HD content or 12 SD content. Currently TVRI East Java is operating and has broadcast 4 types of programs namely; national broadcasts, East Java local broadcasts, sports broadcasts and world broadcasts.